2021
DOI: 10.1016/j.jhazmat.2020.124955
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Performance study of microplastic inhalation risk posed by wearing masks

Abstract: Wearing face masks has become the new normal worldwide due to the global spread of the coronavirus disease 2019. The inhalation of microplastics due to the wearing of masks has rarely been reported. The present study used different types of commonly used masks to conduct breathing simulation experiments and investigate microplastic inhalation risk. Microplastic inhalation caused by reusing masks that underwent various treatment processes was also tested. Results implied that wearing masks considerably reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(145 citation statements)
references
References 29 publications
6
135
4
Order By: Relevance
“…An increasing number of studies are pointing to face masks as an emerging source of plastic pollution that will shortly add-up to the already critical situation ( Patrício Silva et al, 2021 , Prata et al, 2021 ). First evidences of microplastic release from face masks are provided in the recent literature ( Chen et al, 2021 , Saliu et al, 2021 ), also detecting microfibers associated with chemical contaminants ( Sullivan et al, 2021 ) and raising concern for their potential inhalation and ingestion risks ( Li et al, 2021 ). However, there is still a lack of knowledge on the face mask contribution to micro/nanoplastic generation, given that microfibers can be fragmented into thousands of nano-sized particles, more persistent and difficult to be detected ( Henry et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies are pointing to face masks as an emerging source of plastic pollution that will shortly add-up to the already critical situation ( Patrício Silva et al, 2021 , Prata et al, 2021 ). First evidences of microplastic release from face masks are provided in the recent literature ( Chen et al, 2021 , Saliu et al, 2021 ), also detecting microfibers associated with chemical contaminants ( Sullivan et al, 2021 ) and raising concern for their potential inhalation and ingestion risks ( Li et al, 2021 ). However, there is still a lack of knowledge on the face mask contribution to micro/nanoplastic generation, given that microfibers can be fragmented into thousands of nano-sized particles, more persistent and difficult to be detected ( Henry et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, humans have many routes of microplastics exposure such as food (Al-Sid-Cheikh et al 2018 ; Razeghi et al 2021 ; Ribeiro et al 2020 ; Zarus et al 2021 ), food packaging (Zarus et al 2021 ), medical implants (Hicks et al 1996 ; Urban et al 2000 ), and baby bottles (Li et al 2020a ), and multiple studies have found microplastics in human stool samples (Schwabl et al 2019 ; Zhang et al 2020a ). Estimates put human ingestion of microplastics at 40,000–50,000 particles per person per year (Cox et al 2019 ), increasing to 70,000–120,000 particles when including inhalation (Cox et al 2020 ; Prata 2018 ), with possible further exacerbation due to recent increased synthetic mask-wearing due to the COVID-19 pandemic (Li et al 2020c ).…”
Section: Introductionmentioning
confidence: 99%
“… Designed to reflect a realistic situation of microplastics inhalation and no contamination control measures were applied. - VI, LDIR, and Raman Increase in microplastics with time exposure Fiber and spherical type particles; 600 to 1800 μm Li et al, 2021 10 Disposable Face masks of 7 brands (new); colored plain, black Purchased from several manufacturers in China Masks were submerged in 1.5 L deionized water under agitation for 4 h Procedural blanks with each batch by filtering 1.5 L of deionized water Aluminum oxide filter; 0.1 μm VI, SEM, and FTIR - Fiber; PP and PA, dye eriochrome black and congo red; < 25 μm – 2.5 mm; black, blue, and pink Sullivan et al, 2021 Three wet wipes - Each sample was cut into 5 cm×5 cm pieces Experiment I Rubbing wipes for 10 times on gloves and rinsed with 100 mL of DI water Experiment II Immersing wipes in water for 1 h Experiment III Dried wipes at oven were rubbed and followed the steps of experiment I All collected samples were treated with H 2 O 2 All experiments were conducted on a clean bench and stored in glass bottles Petri dishes covered with aluminium foil Procedural blanks with deionized water were conducted Triplicates were carried out for each wipe Anodisc filter; 0.2 μm VI, FESEM, and FTIR Experiment I: 180-200 p/sheet Experiment II: 693–1066 p/sheet Polyester; Fiber, mostly cylindrical smooth shape; 93% of fibers were more than 100 μm Lee et al, 2021 DI: Deionized water; VI: Visual Inspection; LDIR: Laser Direct Infrared Imaging; ATR-FTIR: Attenuated Total Reflection- Fourier-transform infrared spectroscopy; FESEM: Field Emission Scanning Electron Microscopy; AFM: Atomic Force Microscopy. …”
Section: Database Search Inclusion and Exclusion Criteria And Resultsmentioning
confidence: 99%